In 1993 Strehl showed that $$ \sum_k\binom nk^3=\sum_k\binom nk^2\binom{2k}n. $$ I’m interested in a combinatorial proof.

Upd (Jan '14). Maybe the original question was too restrictive — I'm now asking for any proof.

I've written a combinatorial proof (see answers), but it's somewhat convoluted. Maybe there is a nice proof using generating functions / residues (something like one for the Dixon's identity), for example?..

Comments and thoughts

  1. There is of course an algebraic proof (any such identity can be proved using WZ-magic of hypergeometric functions AFAIK). Feel free to post any proof, but I’m mainly interested in a combinatorial proof.
  2. It’s well known that $\sum_k\binom nk=2^n$ and $\sum_k\binom nk^2=\binom{2n}n$. Perhaps, one should think about Stehl identity as the next member of this family. (Is there any analogue for degree 4, I wonder, btw?)
  3. Quadratic case suggests that it’s, perhaps, better to write LHS as $\binom nk^2\binom n{n-k}$. And maybe instead of one $n$ one should introduce two or three parameters (s.t. Strehl identity corresponds to n=m[=l]). A naive approach is $\sum\binom nk\binom mk\binom m{m-k}$ but looks like $\sum\binom nk\binom mk\binom n{m-k}$ might be a better choice — actually, it's equal to $\sum\binom nk\binom mk\binom{2k}m$.
  4. arXiv:0712.3946 might be of some relevance. There LHS is interpreted as the number of ways to deal a deck of 3n cards (n denominations, 3 colors) to 3 players so that no player receives a card of her own color.
  5. Let's write the identity in the form $$ \sum_{i+j=n}\binom Bi\binom Wj\binom ni=\sum_k\binom Bk\binom Wk\binom{2k}n, $$ where $B$ and $W$ are two $n$-element sets. What I want to say is that both sides count ways to choose an $n$-element subset of $B\sqcup W$ with some kind of... extension (cf. two formulas for a trinomial coefficient, perhaps).

2 Answers 2


Suppose we have $n$ black cards and $n$ white cards and we want to divide cards into «good» and «bad» — in such way that there is the same number of bad cards of each color — and burn $n$ of bad cards.

(RHS) Obviously there are exactly $\sum\binom nk^2\binom{2k}n$ ways to do it: we choose $k$ bad black cards, $k$ bad white cards and burn $n$ bad cards.

(LHS) If we just want to choose what $n$ cards we burn — it can be done in $\sum_k\binom nk\binom n{n-k}$ ways: we choose $k$ black cards to burn and $n-k$ white cards to burn.

Let’s call bad white cards and good black cards «perverse». After we’ve burned that $n$ cards we need to choose exactly $k$ perverse cards (from the cards left): if we have $l$ good black cards, we've had $n-l$ bad white cards of which $(n-l)-(n-k)=k-l$ left.

So $$\sum\binom nk^2\binom{2k}n=\sum\binom nk\binom n{n-k}\binom nk.$$

// This is of course just a rewrite of an algebraic proof (based on Vandermonde convolution and aforementioned two presentations of the same trinomial coefficient) — namely, of the proof on p. 16 of V. Strehl’s «Binomial Identities...» (I’ve tried to look into the paper before — but missed it).

  • 1
    $\begingroup$ If you are still following this question you might want to look at my proof. $\endgroup$ Jun 24, 2015 at 1:38
  • $\begingroup$ "we need to choose exactly k perverse cards (from the cards left)": Why exactly $k$? $\endgroup$ Jan 15, 2019 at 21:14
  • $\begingroup$ @darijgrinberg that's explained after the colon $\endgroup$
    – Grigory M
    Jan 15, 2019 at 21:59
  • $\begingroup$ @GrigoryM: Oops! I've failed to realize that the $k$ was being used for something else in the analysis of the RHS than in the LHS. $\endgroup$ Jan 15, 2019 at 22:01

Suppose we seek to show that $$\sum_{k=0}^n {n\choose k}^3 = \sum_{k=\lceil n/2 \rceil}^n {n\choose k}^2 {2k\choose n}.$$


$${n\choose k} {2k\choose n} = \frac{(2k)!}{k!\times (n-k)! \times (2k-n)!} = {2k\choose k} {k\choose n-k}$$

we find that the RHS is $$\sum_{k=\lceil n/2 \rceil}^n {n\choose k} {2k\choose k} {k\choose n-k}.$$

Introduce $${2k\choose k} = \frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{(1+z)^{2k}}{z^{k+1}} \; dz$$

and (this integral is zero when $0\le k\lt \lceil n/2\rceil$) $${k\choose n-k} = \frac{1}{2\pi i} \int_{|w|=\gamma} \frac{(1+w)^{k}}{w^{n-k+1}} \; dw$$

to get for the RHS

$$\frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z} \frac{1}{2\pi i} \int_{|w|=\gamma} \frac{1}{w^{n+1}} \sum_{k=0}^n {n\choose k} \frac{w^k(1+w)^k (1+z)^{2k}}{z^k} \; dw\; dz \\ = \frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z} \frac{1}{2\pi i} \int_{|w|=\gamma} \frac{1}{w^{n+1}} \left(1+\frac{w(1+w)(1+z)^2}{z}\right)^n \; dw\; dz \\ = \frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} \frac{1}{2\pi i} \int_{|w|=\gamma} \frac{1}{w^{n+1}} (z+w(1+w)(1+z)^2)^n \; dw\; dz \\ = \frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} \frac{1}{2\pi i} \int_{|w|=\gamma} \frac{1}{w^{n+1}} (z+w(z+1))^n (1+w(z+1))^n \; dw\; dz.$$

Extracting first the residue in $w$ in next the residue in $z$ we get

$$\frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} \sum_{q=0}^n {n\choose q} z^{n-q} (1+z)^q {n\choose n-q} (1+z)^{n-q} \; dz \\ = \sum_{q=0}^n {n\choose q}^2 \frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{(1+z)^n}{z^{q+1}} \; dz \\ = \sum_{q=0}^n {n\choose q}^3$$


Addendum May 27 2018. We compute this using formal power series as per request in comment. Start from

$${2k\choose k} = [z^k] (1+z)^{2k}$$


$${k\choose n-k} = [w^{n-k}] (1+w)^k.$$

Observe that this coefficient extractor is zero when $n-k\gt k$ or $k\lt\lceil n/2\rceil$ where $k\ge 0.$ Hence we are justified in lowering $k$ to zero when we substitute these into the sum and we find

$$\sum_{k=0}^n {n\choose k} [z^k] (1+z)^{2k} [w^{n-k}] (1+w)^k \\ = [z^0] [w^n] \sum_{k=0}^n {n\choose k} \frac{1}{z^k} (1+z)^{2k} w^k (1+w)^k \\ = [z^0] [w^n] \left(1+\frac{(1+z)^2 w (1+w)}{z}\right)^n \\ = [z^n] [w^n] (z + (1+z)^2 w (1+w))^n \\ = [z^n] [w^n] (1+w(1+z))^n (z+w(1+z))^n.$$

We extract the coefficient on $[w^n]$ then the one on $[z^n]$ and get

$$[z^n] \sum_{q=0}^n {n\choose q} (1+z)^q {n\choose n-q} (1+z)^{n-q} z^q \\ = \sum_{q=0}^n {n\choose q}^2 [z^{n-q}] (1+z)^n = \sum_{q=0}^n {n\choose q}^2 {n\choose n-q} = \sum_{q=0}^n {n\choose q}^3.$$

The claim is proved.

  • 1
    $\begingroup$ Nice. Since you don't really use change of variables etc one can get rid of all integrals and get a slightly shorter version in the language of gen. functions. $\endgroup$
    – Grigory M
    Jun 24, 2015 at 11:20
  • 1
    $\begingroup$ The same argument proves the generalisation $\sum_k \binom{n}{k} \binom{m}{k} \binom{n}{m-k} = \sum_k \binom{n}{k} \binom{m}{k} \binom{2k}{m}$ of comment/thought 3 of the question. $\endgroup$ May 28, 2018 at 11:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.